Morphological characterization using sensory canal pores and pit organs in goby fishes (Gobiidae) in Lake Mainit, Agusan del Norte - Crumb, Danielle Julie Marie (2010)
In this study, the taxonomic status of Goby fishes in Lake Mainit, Agusan del Norte has not been properly established. Through morphological characterization, it could aid in identifying the fishes up to the species level. The arrangement of the sensory canal pores and pit organs on the cephalic region of the fish was used to determine its identity. Thriugh this, it was known that all samples beong to Glossogobus giuris. Color patterns present after 95% ethanol immersion were also observed to evaluate which characteristics belong to this species even after decoloration. Procrustes Analysis was also employed to correlate the fish samples gathered in April 2006 and June 2007 in the study of Cherry Sara (2009) with the May 2009 samples obtained in this study by using the fishes' morphometrics. This yielded the result that the fishes are correlated to one another with a correlation in a symmetric procrustes rotation value of 0.957 and P value of 0.001 which concludes that fish samples collected from both studies are of the same species with respect to the similar season within a year.
Thesis (BS Biology) -- University of the Philippines Mindanao, 2010
Keywords: Glossogogius giuris; Sensory canal pores; Pit organs; Procrustes; Goby fishes -- Lake Mainit, Agusan del Norte; Fishes